Progress and Policy - Hubmann, Georg; Kapeller, Jakob (Momentum Quarterly, 2014)
The concept of progress and the emergence of political visions are closely intertwined. In this context the idea of progress is not only a precondition for understanding politics as a means for governing social change, but also influences political aims as well as political rhetoric. Taking the ambiguous and contested understanding of progress in today’s societies as a starting point, we ask for general criteria suitable for analyzing and understanding the role of progress for policy-making and try to differentiate between various dimensions of progress to arrive at a nuanced argument on how to incorporate progress as an abstract concept into political agenda-setting. Specifically, we look at the prospects and problems, which arise when progress is used as a core frame for policy design.
Keywords: progress; political vision; utopia; values; parties